1997
DOI: 10.1172/jci119429
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation, expression, and apoptotic potential of galectin-9, a beta-galactoside binding lectin.

Abstract: Galectin-9, a ␤ -galactoside binding lectin, has recently been isolated from murine embryonic kidney. In this study, its biological functions and expression in embryonic, newborn, and adult mice tissues were investigated. By Northern blot analyses, it was found widely distributed and its expression was developmentally regulated. In situ hybridization studies revealed an accentuated expression of galectin-9 in liver and thymus of embryonic mice. In postnatal mice, antigalectin-9 immunoreactivity was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
198
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(202 citation statements)
references
References 49 publications
1
198
0
1
Order By: Relevance
“…In addition to the anti-metastatic roles of Gal-9 mentioned above, it had been reported that Gal-9 induced apoptosis in T cells (Wada et al, 1997;Tsuchiyama et al, 2000), malignant melanoma cells (Kageshita et al, 2002) and breast cancer cells (Irie et al, 2005), and the pro-apoptotic role was required for galectin-9-induced suppression of melanoma and breast cancers (Kageshita et al, 2002;Irie et al, 2005). Kobayashi et al (2010) confirmed that Gal-9 exhibits anti-myeloma activity through JNK and p38 MAP kinase pathways.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition to the anti-metastatic roles of Gal-9 mentioned above, it had been reported that Gal-9 induced apoptosis in T cells (Wada et al, 1997;Tsuchiyama et al, 2000), malignant melanoma cells (Kageshita et al, 2002) and breast cancer cells (Irie et al, 2005), and the pro-apoptotic role was required for galectin-9-induced suppression of melanoma and breast cancers (Kageshita et al, 2002;Irie et al, 2005). Kobayashi et al (2010) confirmed that Gal-9 exhibits anti-myeloma activity through JNK and p38 MAP kinase pathways.…”
Section: Discussionmentioning
confidence: 73%
“…The process of metastasis involves five critical steps: detachment of cancer cells from primary sites, movement (invasion) of cancer cells in ECM, attachment of cancer cells to vascular endothelial cells at distal sites, invasion of cancer cells through vascular endothelium, and tumor growth with neovascularization, which are essential for accomplishing malignant tumor metastasis (Wada et al, 1997). According to the present study we can find that Gal-9 suppressed multiple steps of metastasis by promoting cell aggregation, inhibiting adhesion and invasion of cancer cells to ECM, blocking cell-endothelial adhesion and obstructing trans-endothelium invasion of the tumor cells, which supported the hypothesis that Gal-9 prevent metastasis of hepatocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although galectin-1 and -3 have been well studied among the various galectins, we do not have enough information on galectin-9. Wada et al 12 showed that galectin-9 induces mouse thymocyte apoptosis. We have found that HTLV-Iinfected T-cell lines and ATL cells from different patients are more susceptible to growth inhibition induced by treatment with hG9NC(null) than normal PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recent studies suggested that galectin-9 is a modulator of immune functions; it induces chemotaxis of eosinophils 11 and apoptosis of thymocytes, suggesting a possible role in the process of negative selection occurring during T-cell development. 12 With the objective of finding newer agents for the treatment of ATL, the present study was designed to investigate the antitumor potential of galectin-9 on HTLV-I-infected T-cell lines and primary ATL cells in vitro and in vivo, and the possible mechanisms involved in such antitumor activities. Since the protease susceptibility of galectin-9 makes it difficult to efficiently carry out in vivo experiments with recombinant proteins, we used the protease-resistant galectin-9 by modification of its linker peptide, hG9NC(null), in this study.…”
mentioning
confidence: 99%
“…[1][2][3][4] Significant progress has been made in the use of synthetic glycopolymers that mimic the role of carbohydrates in biological systems, to promote cell recognition characteristics. 5 Therefore, biomimetic glycopolymers have been designed to activate cell surfaces and control cell adhesion.…”
Section: Introductionmentioning
confidence: 99%